Stable Flexible Transparent Electrodes for Localized Heating of Lab‐on‐a‐Chip Devices. Issue 1 (10th August 2022) - Papanastasiou, Dorina T.; Sekkat, Abderrahime; Nguyen, Viet Huong; Jiménez, Carmen; Muñoz‐Rojas, David; Bruckert, Franz; Bellet, Daniel
Abstract: In situ biological observations require stable, accurate, and local temperature control of specimen. Several heating elements are coupled with microfluidic systems, but few of them are transparent to visible light and therefore compatible with microscopic observation. Traditional transparent electrodes, such as indium tin oxide, still suffer from high fabrication cost and brittleness, which is not fully compatible to emerging microfluidic devices. Here, a lightweight, low‐cost, flexible transparent heater based on percolating silver nanowire networks, protected with a transparent zinc oxide film, for the in situ monitoring of biological experiments is proposed. Using the fluorescence of dyes bound to double‐stranded DNA to monitor its temperature in situ, it is demonstrated that such nanocomposites allow rapid and reproducible heating under low applied voltage. Furthermore, selective heating is achieved in different zones of the same microchannel or for adjacent microchannels of the chip heating at different temperatures, with a single transparent heater and bias. Abstract : Lightweight, flexible, and highly stable transparent heaters based on silver nanowire networks, are integrated in lab‐on‐a‐chip for in situ monitoring of biological processes. Localized heating using a single transparent heater and applied bias, is demonstrated inside one microchannel or for adjacent microchannels of the same chip heating at different temperatures.